Academic writing - Bailey, Stephen (Routledge, 2014)
Previous edition: 2011; There are four main parts in Academic Writing: The writing process, Elements of writing,Vocabulary for writing, Writing models. Each part is divided into short units which contain examples, explanations and exercises, for use in the classroom or for self-study. The units are clearly organised to allow teachers and students find the help they need with writing tasks, while cross-referencing allows easy access to relevant sections